Alteration of synergistic muscle activity following neuromuscular electrical stimulation of one muscle - Stutzig, Norman (Blackwell Publishing Inc, 2012)
The aim of the study was to determine muscle activation of the m. triceps surae during maximal voluntary contractions (MVCs) following neuromuscular electrical stimulation (NMES) of the m. gastrocnemius lateralis (GL). The participants (n = 10) performed three MVC during pretest, posttest, and recovery, respectively. Subsequent to the pretest, the GL was stimulated by NMES. During MVC, force and surface electromyography (EMG) of the GL, m. gastrocnemius medialis (GM), and m. soleus (SOL) were measured. NMES of GL induced no significant decline (3%) in force. EMG activity of the GL decreased significantly to 81% (P < 0.05), whereas EMG activity of the synergistic SOL increased to 112% (P < 0.01). The GM (103%, P = 1.00) remained unaltered. Decreased EMG activity in the GL was most likely caused by failure of the electrical propagation at its muscle fiber membrane. The decline of EMG activity in GL was compensated by increased EMG activity of SOL during MVC. It is suggested that these compensatory effects are caused by central contributions induced by NMES.